Cushioning capability analysis of seat foundations considering the sitter’s anthropometric dimensions - Hu, Lingling; Tor, Onder; Shen, Liming; Zhang, Jilei; Quin, Franklin; Yu, Xiaohong (BioResources, 2020)
Sitting comfort is primarily determined by the cushioning capability of the seat foundation. Limited literature has been found related to the effects that different sized human buttocks had on the cushioning capability of the seat foundation. Moreover, there is no testing method specialized to measure the load-deformation behavior of foam cushions that imitates the sitting behavior between indenters with different sizes and seat support. This study investigated the effects of various indenter diameters (20 cm, 30 cm, 36 cm, 41 cm, 51 cm, and 58 cm), foam stiffness levels (high and low), and seat bases (spring versus solid flat panel) on the compressive load-deformation behavior of upholstered seat foundations. The load-deformation curves of all the tested foam-seat base combinations exhibited three typical regions, i.e., linear elasticity, plateau, and densification, when subjected to the loads applied through different indenter diameters. Statistical results indicated that the primary effects of the indenter diameter, foam stiffness level, and seat base had significant effects on the spring constants, which represented the slopes of lines in these three regions. In addition, a regression technique was proposed to derive power equations for the estimation of the spring constants of a seat foundation as a function of the indenter diameter, foam material stiffness, and seat base type.